Climate change and agricultural output in the ECOWAS region. (23rd December 2020) - Ogbuabor, Jonathan E.; Orji, Anthony; Manasseh, Charles O.; Anthony-Orji, Onyinye I.
This study examined the impact of climate change on the output of the agricultural sector in Economic Community of West African States (ECOWAS) using 2002-2015 annual panel climatic dataset under the framework of a cross-country agricultural production model. The study accounted for climate change using variations in rainfall and temperature, while model estimation was based on both fixed effect and panel two-stage least-squares techniques. The results indicate that while variations in rainfall exert positive and significant influence on agricultural output in ECOWAS, the influence of temperature variations is negative and insignificant. Other non-negligible output drivers in the agricultural sector in the sub-region are capital and labour. The study concludes that the adoption of agricultural techniques that optimise water use through increased and improved irrigation systems will enhance the output of the sector in ECOWAS.